Risk Factors of Musculoskeletal Disorders among Supermarket Workers in Kajang - Ilyas Syafiq Darul Ridzuan; Brigitte Joan Bernard (Proceeding of International Conference on Science, Health, And Technology, 2022)
Musculoskeletal disorders (MSDs) are injuries which affect the movement of musculoskeletal system of the human body and supermarket workers are prone to develop MSDs due to their tasks by handling material manually. The objectives of this study were to assess the risk factors of MSDs including propose appropriate control measures towards risk reduction. This study was conducted by using Cornell Musculoskeletal Questionnaire as a survey and Rapid Entire Body Assessment (REBA) as an observation method. Among 14 respondents consisted of 12 males and 2 females, the self-reported questionnaires revealed that the most-troubled body part experienced by the respondents in the last one week was shoulder (64.29%), followed by feet (57.14%) and lower back (57.14%). For the REBA score, workers from fresh market department and grocery department reported to had medium risk level of awkward posture. In general, most supermarket workers were had to stand and use their upper limbs while conducting the tasks. Intervention in terms of administrative controls such as to change the way of people work and job rotation could minimize the risk of developing MSDs among supermarket workers.